A method to significantly improve the yield strength of nanocrystalline VCoNi medium-entropy alloys via order-disorder phase transition

By controlling the annealing temperature in metal nanocrystalline materials and using inert gas condensation method and ultra-high pressure technology to prepare nanocrystalline VCoNi medium-entropy alloys, the problems of limited strength improvement amplitude and complex process in the existing technology are solved, and the effect of efficiently and significantly improving yield strength is achieved.

CN116411212BActive Publication Date: 2025-04-29NANJING UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310167368.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-27
Publication Date
2025-04-29
Estimated Expiration
2043-02-27

AI Technical Summary

Technical Problem

The prior art has problems such as limited amplitude, complex process and high energy consumption in improving the strength of metal structure materials, and it is difficult to significantly improve the yield strength of high-entropy alloys.

Method used

By controlling the annealing temperature, the metal nanocrystalline material matrix undergoes an orderly and disorderly transformation. Nanocrystalline VCoNi medium entropy alloy is prepared by inert gas condensation method and in situ ultra-high pressure technology. The specific steps include smelting, homogenization treatment, large deformation cold rolling, inert gas condensation and ultra-high pressure forming, and finally conducting an insulation annealing experiment at 600°C.

Benefits of technology

The yield strength of nanocrystalline VCoNi medium entropy alloy was significantly improved, from 3.4GPa to 5.7GPa, with an increase of up to 67.6%, and the process flow was simplified and energy consumption was reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116411212B_ABST
    Figure CN116411212B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of metal material phase transition, and discloses a method for significantly improving the yield strength of nanocrystalline VCoNi medium entropy alloy through ordered-disorder phase transition. First, a high-purity medium entropy VCoNi bulk material is prepared by a vacuum arc melting furnace; then, the bulk material is subjected to a structural homogenization treatment by large plastic deformation (cold rolling) and heat treatment; then, a bulk material is prepared by laser inert gas condensation and ultra-high pressure; finally, an annealing process is performed to make the material undergo an ordered-disorder transition, thereby achieving a significant improvement in strength. Traditional strengthening methods often require cumbersome processes, huge time and financial investment, and the strengthening range is limited. The strengthening method provided by the present invention is not only simple to operate, but also can save time and financial investment costs; the ordered-disorder transition involved has strong scalability, and materials that can undergo an ordered-disorder phase transition under certain conditions can be designed based on this, thereby greatly improving the mechanical properties of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of metal material phase change, and in particular to a method for significantly improving the yield strength of nanocrystalline VCoNi medium entropy alloy through ordered-disordered phase change. Background Art

[0002] With the continuous development of human society and the continuous progress of science and technology, the service conditions of various engineering structural materials are becoming more and more harsh. Traditional metal structural materials have gradually been unable to meet the needs of social development. The research and development of new high-performance alloys is the top priority of current scientific research. In recent years, medium- and high-entropy alloys have gradually become a new type of engineering structural material with broad market application prospects due to their many excellent physical and chemical properties, and have become a hot topic of current research. VCoNi medium-entropy alloys have excellent mechanical properties due to their large lattice distortion effect and Hall-Petch coefficient: the yield strength is as high as nearly 1GPa when the average grain size is 1μm. Therefore, how to effectively improve its mechanical properties through reasonable and scientific organizational regulation is the key to promoting the future development and application of such materials.

[0003] Theoretical studies have shown that there are four main methods to improve the strength of metal structural materials: fine grain strengthening, solid solution strengthening, second phase strengthening, and work hardening. The essence of these four types of strengthening is to form a stress field inside the material matrix, thereby hindering dislocation movement and ultimately achieving strength improvement. However, these four methods have limited effects on improving material strength and cannot significantly improve the strength of metal structural materials, and thus cannot significantly improve their service performance.

[0004] After searching, the Chinese patent document with the publication date of August 16, 2022 and the publication number of CN 112547798 B discloses a method for preparing high-strength heterogeneous high-entropy alloys by cumulative rolling. This method successfully prepares a high-entropy alloy with two grain sizes by combining cumulative rolling with heat treatment process. Due to the back stress strengthening effect, the alloy has a good strength-plasticity match, but the highest value of its reported yield strength is still less than 2000MPa, which is not significantly improved compared with the directly cast parent material.

[0005] The Chinese patent document with the publication date of October 14, 2022 and the publication number of CN 115141989 A discloses a method for improving the laser selective melting of AlSi 10Method for improving the strength of Mg alloy. The invention regulates the heat treatment process to precipitate dispersed GP zones or β″ (Mg2Si) strengthening phases in the matrix structure. The dispersed precipitated phases can produce a strong pinning effect on dislocations, thereby significantly improving the strength of the material. Through this method, the maximum value of the yield strength improvement of the material is 26.1%, which is still within the range achievable by other processes and has not been significantly improved.

[0006] After searching, the Chinese patent document with the publication date of July 12, 2022 and the publication number of CN 112662931 B discloses a method and product for simultaneously improving the strength and plasticity of austenitic steel. This invention patent achieves strength improvement by regulating parameters such as twins, dislocations, precipitated phases and grain size inside the matrix through large plastic deformation and heat treatment, but the magnitude of the strength improvement does not exceed 30%, and the absolute value of its yield strength has not yet reached 1GPa, which has limited driving effect on the development of engineering applications of such materials.

[0007] After searching, a Chinese patent document with a publication date of November 11, 2022 and publication number CN 115323241 A discloses a method for preparing a nano-refractory high-entropy alloy TiZrHfNb. This method successfully prepares nanocrystalline materials with uniform structure and good thermal stability by combining inert gas condensation with ultra-high pressure. This method not only provides a new idea for the preparation of metal nanocrystalline materials, but its nano-scale grain size (less than 20nm) also provides huge space for the subsequent regulation of its performance.

[0008] In summary, although the current mainstream strengthening methods can effectively improve the strength of metal structural materials to a certain extent, the improvement is limited and the preparation process is complex and energy-intensive. Given the characteristics of nanostructures that are prone to phase transition in a high-energy state, if metal nanocrystalline materials with sufficiently small grain sizes can be prepared, their microstructures can be reasonably regulated, so that the entire matrix of the material undergoes an order-disorder transition, and then the yield strength can be greatly improved on this basis, this will have a huge driving effect on the development of metal structural material strengthening theory and its potential future applications. Summary of the invention

[0009] The purpose of the present invention is to provide a method for significantly improving the yield strength of nanocrystalline VCoNi medium-entropy alloys through ordered-disordered phase transition, which solves the problem that although the current mainstream strengthening means proposed in the background technology can effectively improve the strength of metal structural materials to a certain extent, the improvement is limited and the preparation process is complex and the energy consumption is high.

[0010] To achieve the above object, the present invention provides the following technical solution: a method for significantly improving the yield strength of nanocrystalline VCoNi medium entropy alloy through ordered-disordered phase transition, comprising the following preparation steps:

[0011] S1: The chemical elements in the VCoNi alloy are in the following ratio: V:Co:Ni=1:1:1; and the purity of the single element of the smelting parent material is ≥99.95%. The surface of the raw material is polished and cleaned to remove possible oxidation on the surface, and then weighed on a balance;

[0012] S2: Since the melting point of element V is significantly higher than that of other elements, in order to ensure uniform element distribution of the sample prepared in S1, the three raw materials should be placed in the melting chamber with element V at the top;

[0013] S3: homogenizing the prepared bulk alloy at a temperature of 1100° C.-1200° C. for 10-12 hours, and then performing large deformation cold rolling on the bulk alloy;

[0014] S4: Deposit powder materials using inert gas condensation method and prepare them into bulk materials through in-situ ultra-high pressure. The specific process is as follows: Before the experiment, the entire inert gas condensation chamber is carefully cleaned to avoid potential impurity contamination sources, and the target material prepared in the previous step is placed on the sample tray in the chamber;

[0015] S5: The cavity is then pumped to an ultra-high vacuum state by a mechanical pump and a molecular pump, and then high-purity helium is slowly injected into the cavity, and then liquid nitrogen is injected into the cold trap; the initial position of the laser is set and its angle is adjusted so that the optical path is perpendicular to the target, and the distance between the laser and the sample is set;

[0016] S6: Determine the laser power and conduct a short test experiment to ensure that the laser evaporation, cold trap deposition and scraper collection of the powder can be successfully achieved after the laser interacts with the bulk material;

[0017] S7: After collecting enough powder, the powder collection tank is transferred in situ to a low-pressure chamber in an oxygen-free environment. The sample is then transferred in situ to a high-pressure chamber in an oxygen-free environment and pressurized at 5-6 GPa for 3 minutes. Finally, high-purity bulk nanocrystalline materials are successfully prepared.

[0018] S8: The material prepared by the above process is subjected to a heat preservation annealing experiment to make it undergo an order-disorder transformation, and then its microstructure and properties are characterized.

[0019] As a preferred embodiment of the present invention, in S1, the block sample is melted in a vacuum arc melting furnace.

[0020] As a preferred embodiment of the present invention, the final rolling amount of S2 is controlled at 50%-80%.

[0021] As a preferred embodiment of the present invention, in order to ensure uniform distribution of elements in the prepared material, the smelting is repeated six times in S2.

[0022] As a preferred embodiment of the present invention, in S2, annealing is performed at 1000-1200° C. for 3-6 hours under a vacuum environment to obtain a bulk material with uniform microstructure.

[0023] As a preferred embodiment of the present invention, the vacuum value in S5 is <10 -6 Pa.

[0024] As a preferred embodiment of the present invention, in S6, after ensuring that there are no problems, the powder making experiment is started, the powder making process is observed in real time through a reserved observation window, and the nanopowder that has been deposited on the cold trap is carefully scraped off with a scraper in a timely manner and collected in a powder collecting tank.

[0025] As a preferred embodiment of the present invention, in S7, a pressure of 500-800 MPa is used to perform pre-pressing molding.

[0026] As a preferred embodiment of the present invention, the insulation temperature in S8 is 600°C.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] a. Traditional strengthening methods have limited effect on improving the strength of metal structural materials, and their strengthening effect is almost negligible for materials with high basic strength. The present invention controls the annealing temperature to cause an ordered-disordered transformation of the metal nanocrystalline material matrix, thereby increasing the yield strength of the VCoNi medium-entropy alloy from 3.4 GPa to 5.7 GPa, an increase of nearly 2.3 GPa, and an increase of up to 67.6%. For materials with high basic strength, the improvement of this invention is significantly higher than the currently reported strengthening methods for metal structural materials.

[0029] b. Traditional strengthening methods often require complicated processes, huge time and capital investment, and the strengthening range is limited. The strengthening method provided by the present invention is not only simple to operate, but also can save time and capital investment costs.

[0030] c. The order-disorder transition involved in this invention has strong scalability, and can be used to design materials that can undergo order-disorder phase transition under certain conditions, thereby greatly improving the mechanical properties of the materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0032] Figure 1 It is a schematic diagram of the inert gas condensation device.

[0033] Figure 2 These are the TEM characterization results and grain size distribution diagram of the as-prepared nanocrystalline VCoNi medium-entropy alloy: (a) bright field image; (b) dark field image; (c) SAED diffraction pattern; (d) grain size distribution diagram.

[0034] Figure 3 It is the compressive true stress-strain curve of the prepared state and the 600℃ annealed state.

[0035] Figure 4 It is an in situ synchrotron radiation X-ray diffraction pattern. DETAILED DESCRIPTION

[0036] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further explained below in conjunction with specific implementation methods.

[0037] See also Figure 1-4 The present invention provides a technical solution: a method for significantly improving the yield strength of nanocrystalline VCoNi medium entropy alloy through ordered-disordered phase transition, comprising the following preparation steps:

[0038] S1: The chemical elements in the VCoNi alloy are in the following ratio: V:Co:Ni=1:1:1; and the purity of the single element of the smelting parent material is ≥99.95%. The surface of the raw material is polished and cleaned to remove possible oxidation on the surface, and then weighed in a balance, and the block sample is melted in a vacuum arc melting furnace;

[0039] S2: In view of the fact that the melting point of V is significantly higher than that of other elements, in order to ensure uniform element distribution of the S1 sample, the three raw materials should be placed in the melting chamber with V at the top, and the final rolling amount should be controlled at 50%-80%. Then, annealing is carried out at 1000-1200℃ for 3-6h in a vacuum environment to finally obtain a block material with uniform microstructure.

[0040] S3: homogenizing the prepared bulk alloy at a temperature of 1100°C-1200°C for 10-12h, followed by large deformation cold rolling. To ensure uniform distribution of elements in the prepared material, the alloy is repeatedly melted six times.

[0041] S4: Deposit powder materials using inert gas condensation method and prepare them into bulk materials through in-situ ultra-high pressure. The specific process is as follows: Before the experiment, the entire inert gas condensation chamber is carefully cleaned to avoid potential impurity contamination sources, and the target material prepared in the previous step is placed on the sample tray in the chamber;

[0042] S5: The cavity is then pumped to an ultra-high vacuum state using a mechanical pump and a molecular pump, with a vacuum value of <10 -6 Pa, then slowly flush high-purity helium into the cavity, and then flush liquid nitrogen into the cold trap; then set the initial position of the laser and adjust its angle so that the light path is perpendicular to the target, and at the same time set the distance between the laser and the sample;

[0043] S6: Determine the laser power and conduct a short test experiment. After ensuring that there are no problems, start the powder making experiment. Observe the powder making process in real time through the reserved observation window. Use a scraper to carefully scrape off the nanopowder that has been deposited on the cold trap and collect it in the powder collecting tank to ensure that the laser evaporation, cold trap deposition and scraper collection of the powder can be successfully achieved after the interaction between the laser and the bulk material.

[0044] S7: After collecting enough powder, the powder collection tank is transferred in situ to a low-pressure chamber in an anaerobic environment. The sample is then transferred in situ to a high-pressure chamber in an anaerobic environment. It is pre-pressed at a pressure of 500-800 MPa and pressed at a pressure of 5-6 GPa for 3 minutes. Finally, a high-purity bulk nanocrystalline material is successfully prepared.

[0045] S8: The material prepared by the above process is subjected to annealing experiment at 600°C to make it undergo order-disorder transformation, and then its microstructure and properties are characterized.

[0046] Experimental example:

[0047] See also Figure 1-4 The present invention can be divided into four main processes, namely: smelting of VCoNi medium entropy alloy target, homogenization of target structure, deposition of nanoparticles and order-disorder transformation during annealing. The specific experimental process is as follows:

[0048] First, the mass of each element in the VCoNi entropy alloy was calculated and weighed according to the atomic ratio, and the purity of the base material element was controlled to be greater than 99.95%. The surface of the raw material was polished to remove the possible oxidation contamination layer on the surface, and then it was ultrasonically cleaned with alcohol, and then high-precision weighing was performed (the weighing accuracy was controlled within 5×10 -4 g or less);

[0049] The arc melting furnace cavity is then cleaned and evacuated until the vacuum degree in the cavity reaches 1.5×10-3 When the pressure reaches 500 Pa, high-purity argon gas is backwashed into the chamber to about 500 Pa, and then vacuum treatment is carried out, and this process is repeated three times;

[0050] Then put the high-purity raw materials prepared in the first step into the vacuum arc melting furnace (given that the melting point of V element is much higher than that of the other two elements, V element is placed above the other two elements to ensure the uniformity of the smelting structure). Before smelting, pure Ti is repeatedly smelted three times in the cavity to remove the oxygen element that may remain in the cavity. Then, the VCoNi target smelting test is carried out. To ensure the uniformity of smelting, the smelting process is repeated 6 times, and then it is made into 6×20×18mm by vacuum suction casting. 3 of bulk material;

[0051] The prepared material is then homogenized (1100°C in a vacuum environment for 10 hours), and then the sample is subjected to a large deformation cold rolling experiment (5% of the pressing amount each time, and the final rolling amount is controlled at 60%), and then the material is recrystallized at 1000°C for 3 hours in a vacuum environment to ensure that a target material with uniform structure is obtained;

[0052] Then clean the entire inert gas condensation chamber to prevent impurity elements from contaminating the sample. Place the target prepared in the previous step on the sample tray in the chamber, and pump the inert gas condensation chamber to an ultra-high vacuum state (<10 -6 Pa), and then high-purity helium is injected into the cavity and liquid nitrogen is injected into the cold trap (such as Figure 1 shown);

[0053] Then set the initial position of the laser and adjust its angle so that the light path is perpendicular to the target. At the same time, set the distance between the laser and the sample to 75 cm, set the laser power to 100 W, ensure that the single pulse energy exceeds 100 μJ, the pulse frequency is 500 kHz, and the pulse width is less than 15 ps. Then conduct a short test experiment to ensure that the laser evaporation, cold trap deposition and scraper collection of the powder can be successfully achieved after the interaction between the laser and the target.

[0054] After ensuring the success of powder making, start the deposition experiment, observe the powder making process through the observation window reserved in advance, and use a scraper to scrape off the nano powder that has been deposited on the cold trap and collect it in the powder collecting tank;

[0055] After collecting enough powder, the powder collection tank is transferred in situ to a low-pressure chamber in an oxygen-free environment, and pre-pressed at a pressure of 500 MPa. The sample is then placed on the lower pressure head and transferred in situ to a high-pressure chamber, where it is pressed at a pressure of 5 GPa for 3 minutes. Finally, a bulk nanocrystalline material with a diameter of 10 mm and a thickness of 0.3 mm is successfully prepared.

[0056] The bulk nanocrystalline material prepared above was then subjected to an annealing experiment at 600°C for one hour to cause an order-disorder transition. Subsequently, the prepared and annealed states were subjected to TEM sample preparation and small column preparation experiments with a diameter of about 2 μm using a focused ion beam. The characterization results are shown in Figure 2. Figure 2 shown.

[0057] Then nanoindentation (strain rate 10 -2 s -1 ) characterizes its mechanical properties. The yield strength of the prepared state is as high as 3.4 GPa, and the yield strength at 600℃ is as high as 5.7 GPa. Figure 3 shown.

[0058] Further verification experiments were conducted using the Beijing Synchrotron Radiation Facility (3W1, wavelength 0.0206468 nm, high temperature device Linkam TS1200): the bulk nanocrystals prepared in step 8 were placed in a high temperature device for variable temperature XRD experiments (such as Figure 4 As shown in the figure), the heating rate is 20K / min. From the analysis of the main peak position, it can be seen that at around 500℃, the matrix material undergoes an order-disorder transition with a smaller lattice constant.

[0059] It should be noted that the present invention is a method for significantly improving the yield strength of nanocrystalline VCoNi medium-entropy alloys through ordered-disordered phase transitions. Each component is a universal standard component or a component known to those skilled in the art, and its structure and principle can be known to those skilled in the art through technical manuals or through conventional experimental methods.

[0060] Working principle: First, calculate the required mass of each element according to the element ratio, polish and clean the surface of the raw materials to remove possible oxidation on the surface, then weigh them on a balance, and then melt the block sample in a vacuum arc melting furnace (given that the melting point of the V element is significantly higher than that of the other elements, in order to ensure the uniform distribution of elements in the sample preparation, the three raw materials should be placed at the top when they are placed in the melting chamber). Ensure that the elements in the prepared material are evenly distributed, and the melting process is repeated six times. Secondly, the prepared bulk alloy is homogenized (1100℃-1200℃, 10-12h), and then subjected to large deformation cold rolling. The final rolling amount is controlled at 50%-80%, and then annealed at 1000-1200℃ for 3-6h in a vacuum environment to finally obtain a bulk material with uniform microstructure. Then, the powder material is deposited by the inert gas condensation method and prepared into a bulk material by in-situ ultrahigh pressure. The specific process is as follows: ① Before the experiment, the entire inert gas condensation chamber is carefully cleaned to avoid potential impurity contamination sources, and the target material prepared in the previous step is placed on the sample tray in the chamber; ② The chamber is pumped to an ultrahigh vacuum state (<10 -6Pa), then slowly flush high-purity helium into the cavity, and then flush liquid nitrogen into the cold trap; ③ Set the initial position of the laser and adjust its angle so that the light path is perpendicular to the target material, and set the distance between the laser and the sample; ④ Determine the laser power for a short test experiment to ensure that the laser evaporation, cold trap deposition and scraper collection of the powder can be successfully achieved after the laser interacts with the bulk material; ⑤ Start the powder making experiment after ensuring that there are no problems, observe the powder making process in real time through the reserved observation window, and carefully use a scraper to scrape off the nanopowder that has been deposited on the cold trap and collect it in a powder collecting tank; ⑥ After collecting enough powder, transfer the powder collecting tank in situ to a low-pressure chamber in an oxygen-free environment, pre-press it with a pressure of 500-800MPa, and then transfer the sample in situ to a high-pressure chamber in an oxygen-free environment, press it with a pressure of 5-6GPa for 3 minutes, and finally successfully prepare high-purity bulk nanocrystalline materials. Finally, the material prepared by the above process was subjected to a 600°C insulation annealing experiment to make it undergo an order-disorder transformation, and then its microstructure and properties were characterized.

Claims

1. A method for significantly improving the yield strength of nanocrystalline VCoNi medium entropy alloys by order-disorder phase transition, characterized in that: The method comprises the following preparation steps: S1: The chemical elements in the VCoNi alloy are in the following ratio: V:Co:Ni=1:1:1; and the purity of the single element of the smelting parent material is ≥99.95%. The surface of the raw material is polished and cleaned to remove the surface oxidation, and then weighed on a balance; S2: Put the above raw materials into vacuum arc, remelt 6 times, and then vacuum cast them into mm 3 For bulk materials, the three raw materials should be placed in the smelting chamber with the V element at the top; S3: The block material in the above step is homogenized at a temperature of 1100°C-1200°C for 10-12 h, and then subjected to large deformation cold rolling, and then subjected to homogenization, and kept at 1100°C in a vacuum environment for 10 h, and then subjected to large deformation cold rolling experiments, with a pressing amount of 5% each time, and the final rolling amount controlled at 60%, and then subjected to recrystallization treatment at 1000°C for 3 h in a vacuum environment to ensure that a target material with uniform structure is obtained; S4: Before the experiment, the entire inert gas condensation chamber is carefully cleaned to avoid potential impurity contamination sources, the target material prepared in the previous step is placed on the sample tray in the chamber, and the entire inert gas condensation chamber is cleaned again to avoid impurity elements from contaminating the sample, the target material prepared in the previous step is placed on the sample tray in the chamber, the inert gas condensation chamber is pumped to an ultra-high vacuum state by a mechanical pump and a molecular pump, and then high-purity helium is flushed into the chamber and liquid nitrogen is flushed into the cold trap; S5: Determine the laser power and conduct a short test experiment to ensure that the laser evaporation, cold trap deposition and scraper collection of the powder can be successfully achieved after the laser interacts with the bulk material. Set the initial position of the laser and adjust its angle so that the light path is perpendicular to the target material. Set the distance between the laser and the sample to 75 cm and the laser power to 100 W. Ensure that the single pulse energy exceeds 100 μJ, the pulse frequency is 500 kHz, and the pulse width is less than 15 ps. Conduct a short test experiment to ensure that the laser evaporation, cold trap deposition and scraper collection of the powder can be successfully achieved after the laser interacts with the target material. After ensuring the success of powder making, start the deposition experiment, observe the powder making process through the observation window reserved in advance, and use a scraper to scrape off the nano powder that has been deposited on the cold trap and collect it in the powder collecting tank; S6: After collecting enough powder, the powder collecting tank is transferred in situ to a low-pressure chamber in an oxygen-free environment. Then, the sample is transferred in situ to a high-pressure chamber in an oxygen-free environment. A pressure of 5-6 GPa is applied for 3 minutes, and finally a high-purity bulk nanocrystalline material is successfully prepared: S7: The material prepared in the above steps is subjected to a heat preservation annealing experiment to make it undergo an order-disorder transformation, and then its microstructure and performance are characterized.

Citation Information

Patent Citations

  • A method for preparing high-strength heterogeneous high-entropy alloys by cumulative rolling

    CN112547798B

  • A method and product for simultaneously improving the strength and plasticity of austenitic steel

    CN112662931B

  • Method for improving strength of selective laser melting AlSi10Mg alloy

    CN115141989A

  • Preparation method of high-strength and high-toughness aluminum-magnesium alloy with nanosheet layer structure

    CN114086039A

  • TiZrHfNb nanocrystalline refractory high-entropy alloy and preparation method thereof

    CN115323241A